Implementation of Sapta Pesona at Mandala Wangsit Siliwangi Museum - Nisa Permata Dewi (Publikasi Indonesia, 2023)
Museum Mandala Wangsit Siliwangi is one of the historical tourist destinations located in the city of Bandung. One of the aspects of managing tourist destinations is by implementing the 'Sapta Pesona' in Indonesia. However, in reality, there are discrepancies, one of which can be observed in terms of the level of beauty, hospitality, and memories that do not align with visitors' expectations. Therefore, this research aims to understand the implementation of 'Sapta Pesona' at the Museum Mandala Wangsit Siliwangi and to identify the efforts made by the Museum Mandala Wangsit Siliwangi management to enhance the quality of visitor experiences in the future. This study utilizes a descriptive qualitative method. Data collection techniques involve interviews and observations, supported by relevant journal literature related to the research topic. The research findings reveal disparities in the application of 'Sapta Pesona' at the Museum Mandala Wangsit Siliwangi, which affects both the implementation of 'Sapta Pesona' and the quality of visitor experiences. With this research, it is hoped that there will be an improvement in the implementation of 'Sapta Pesona' to enhance the quality of visitor experiences.